Integrative assessment of river damming impacts on aquatic fauna in a Portuguese reservoir - Santos, R.M.B.; Sanches Fernandes, L.F.; Cortes, R.M.V.; Varandas, S.G.P.; Jesus, J.J.B.; Pacheco, F.A.L. (The Science of the total environment, 2017)
The impacts of river damming on aquatic fauna are assessed and then integrated across hierarchical scales, portrayed as nested circles. The outer circles characterize the studied site for habitat disturbance and hydrologic regime during the construction and filling phases. The inner circles characterize the construction and filling phase zones for water quality parameters and aquatic fauna. The procedure for integrating the impacts comprises two consecutive stages: in the task stage, inner circles are characterized through field and laboratory work involving sampling and analyses of water aliquots and aquatic fauna; in the impact assessment stage, circle data are processed in ecological and statistical algorithms, which allow identification of changes in abundance and composition of aquatic fauna communities and their integration with changes in water quality parameters across the construction and filling phase zones. The integrative assessment of river damming impacts on aquatic fauna was carried out in the Sabor River dam (Portugal). This dam created two reservoirs: primary and secondary. Changes in water quality caused by dam construction and stream water impoundment were significant, marked by increases in temperature and electric conductivity downstream, accumulation of phosphorus and nitrogen in the reservoirs triggering the growth of algae and the increase of chlorophyll a, and drop of transparency. These changes were aggravated in the secondary reservoir. The consequences of water deterioration for aquatic fauna were severe, marked by abrupt declines of native fish species and invasion of exotic species even upwards the reservoirs. The ecological status determined from ecological quality ratios of benthic macroinvertebrate assemblages were also affected, changing from good-fair in the unaffected watercourses to fair-poor in the lakes. [Display omitted] •We present an integrative assessment of damming impacts on aquatic fauna.•The integration is made across hierarchical scales.•The impact assessment is applied to construction and filling phases of dam reservoirs.•Habitat fragmentation and water quality degradation produced exotic species invasion.•Water quality and aquatic fauna differ among undisturbed streams and dam reservoirs.